PENGARUH BRAND AMBASADOR DAN BRAND PERSONALITY TERHADAP MINAT BELI PADA PENGGUNA SKINCARE POND’S - Lita Eka Cahyani Putri; Siti Ning Farida (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
Interest in the brand of a company product can certainly generate interest in consuming or knowing more about a product. The purpose of this study is to find out how much influence Brand ambassadors and Brand personality have on buying interest in Pond's skincare products for Pond's product customers at the Wonokromo Village Cosmetic Center. This research is a type of quantitative research because the data comes from the answers of respondents through the distribution of written instruments, namely questionnaires. The use of this method is used in accordance with the intent and purpose of the variabel measurement scale using a Likert scale, which consists of 5 scales. The population of this study are consumers who buy Pond's products at the Wonokromo Village Cosmetic Center who are users of Pond's skincare products. Based on the Slovin formula, the sample in this study was 400 respondents. The sampling method in this study is probability sampling. Data analysis techniques used in this study include validity and reliability tests. Analysis of the data used is multiple linear regression analysis